Aluminium-induced crystallization of silicon thin film by excimer laser annealing - Siti Noraiza Ab Razak; Noriah Bidin (Universiti Kebangsaan Malaysia, 2013)
Polycrystalline silicon (poly-Si) film was fabricated by indirect process of re-crystallization of amorphous silicon (a-Si) thin film. This enhancement process is important to determine the performance of silicon thin film (STF). In this attempt, a fundamental study was carried out to enhance the crystallization of aluminium doped silicon thin film. An a-Si thin film was prepared by low pressure physical vapour deposition (PVD) and doped with 10% aluminium. The aluminium-induced crystallization (AIC) process was carried out in two sequence steps. Firstly, the amorphous film was annealed by using conventional heat treatment at operating temperature of 350°C. Secondly, the poly-Si underwent excimer laser anneling (ELA). The microstructure of thin film was analyzed using atomic force microscope (AFM). The results showed that, the grain size of the a-Si film is increased with the energy density of the excimer laser. The optimum grain size obtained is 129 nm corresponding to energy density of 356 mJ cm-2.